1984
DOI: 10.1007/bf00175378
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of 4-demethoxydaunorubicin (idarubicin) with single oral doses

Abstract: Twenty-four patients with a variety of solid tumors entered a Phase I trial with 4-demethoxydaunorubicin, a new analogue of daunorubicin. The drug was given as a single oral dose of 10-60 mg/m2 repeated every 3-4 weeks. Leukopenia was the dose-limiting toxicity. Other toxic effects included mild to moderate nausea and vomiting. Sixty mg/m2 was found to be the maximum tolerated dose in patients with fair tolerance to chemotherapy and normal liver function. Similar hematologic toxicity was reported in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 5 publications
3
13
1
Order By: Relevance
“…These results agree with the observation of a disappearance of nuclear fluorescence in colon cancer cells cultivated for 1 day or longer in the presence of DX (Chauffert et al, 1984 (Hill et al, 1985). Some anthracyclines showed a low RI like 4-demethoxy-DNR (RI=3) and 4'-deoxy-DX (RI=30) and these data too are in accordance with experimental and clinical trials (Ferrari et al, 1984;Kaplan et al, 1984;Hill et al, 1985). 4'-Deoxy-4'-iodio-DX was cytotoxic on B16VDXR to the same extent as that on B16V.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results agree with the observation of a disappearance of nuclear fluorescence in colon cancer cells cultivated for 1 day or longer in the presence of DX (Chauffert et al, 1984 (Hill et al, 1985). Some anthracyclines showed a low RI like 4-demethoxy-DNR (RI=3) and 4'-deoxy-DX (RI=30) and these data too are in accordance with experimental and clinical trials (Ferrari et al, 1984;Kaplan et al, 1984;Hill et al, 1985). 4'-Deoxy-4'-iodio-DX was cytotoxic on B16VDXR to the same extent as that on B16V.…”
Section: Discussionsupporting
confidence: 89%
“…Pleiotropic drug-resistance has been reported for many different cell lines (Kaye & Merry, 1985). We tested, therefore, whether B16VDXR cells were sensitive to the cytotoxic action of other anthracyclines and of anticancer drugs having (Ferrari et al, 1984;Kaplan et al, 1984;Holdener et al, 1985), and 4'-deoxy-4'-iodio-DX, because it has been shown to be active on the DX-resistant P388 cell line (Facchinetti et al, 1984). VCR, a typical DX cross-resistant drug (Wilkoff & Dulmadge, 1978), and cis-DDP, a non DX crossresistant drug (Seeber et al, 1982), were also tested.…”
Section: Stability Of Resistancementioning
confidence: 99%
“…Nausea and vomiting occurred even with routine antiemetic drug administration but were tolerable. These results are in agreement with other studies [4,6,[9][10][11][12][13] that showed nausea and vomiting were common and that a more aggressive use of antiemetic drugs should be considered. Mucositis was uncommon in our study, and none occurred in three previously reported studies using 4-DMDR doses between 10 and 50 mg/m 2 [7,10,12].…”
Section: Discussionsupporting
confidence: 83%
“…Preclinical toxicologic studies suggested an increased therapeutic index of DMDR compared to DNR and DX, particularly as regards cardiotoxicity (3). In phase I trials (4,5), the acute toxicity was similar to that of DNR and DX but with lower incidence of gastrointestinal side effects as well as alopecia. There was also evidence of tumor responses in patients with NHL (4).…”
Section: Introductionmentioning
confidence: 86%